Avaliação da produção e concentração viral em pimentão infectado por tospovírus com o uso de piraclostrobina + metiram - Spadotti, David Marques de Almeida [UNESP] (2016)
The cultivars of pepper (Capsicum annuum L.) are usually susceptible to virus infection, especially by the species of the genus Potyvirus, Begomovirus, Cucumovirus, Tobamovirus and Tospovirus in Brazil. GRSV (Groundnut ring spot virus) and TCSV (Tomato chlorotic spot virus) are the main tospovirus species in São Paulo state. Due to the large host circle of tospovirus and inefficient chemical vector control (thrips) in the virus transmission, the integrated management of the disease is essential. Thus, the aim of this study was to evaluate the use of chemical defensive Pyraclostrobin + Metiram (P + M) as an alternative form of control of tospoviruses GRSV and TCSV in the pepper hybrid Dahra RX, assessing the quantitative and qualitative production of the plant and the product's influence on the concentration of viral particles of GRSV. Three experiments were carried out in parallel, two in the field, one which received pre-treatment by applying P + M (4 g. L -1) on the tray. In the greenhouse experiment, the pre-treatment consisted by application of P + M (4 g. L -1) in the transplanting of 50% of the plants (total 120 plants). The treatments consisted of inoculation of the virus naturally in the field and sap transmission in greenhouse at 0, 15, 30, 45 days after transplanting (DAT) with application or not of P + M (4.0 g. L -1) during cultivation. Infection by GRSV / TCSV virus was confirmed by PTA-ELISA and virus concentration was evaluated by qPCR for plants in greenhouse. In the greenhouse experiment was obtained 98% of infected plants sap transmitted, while 25% of the plants in the field were naturally infected by GRSV or TCSV, but with predominance of GRSV. Infection of plants of this hybrid by GRSV and TCSV until 45 days after transplantation caused considerable damage in the quality and quantity of fruits produced. The use of the product during the cultivation of the hybrid did not affect the production parameters. Under greenhouse conditions, the seedlings treated at transplanting with P + M had lower total production, indicating that the model adopted for the application of the product was not efficient. The viral concentration of GRSV at 70 DAT was not altered by the use of the product, indicating little effect of suppression of the virus and disease.